Preliminary Assessment of Individual Zone of Optimal Functioning Model Applied to Music Performance Anxiety in College Piano Majors - Yao, Zijin; Li, Yue (Frontiers in Psychology, 2022)
Individual Zone of Optimal Functioning (IZOF) is a psychological model studied and applied to quantification of athletes' anxiety and performance prediction in sports competition. Performance anxiety may occur in both athletes and musicians, and the causes may be similar. Therefore, this study aimed to evaluate application of the IZOF model to evaluate music performance anxiety (MPA) in pianists. College-level piano majors from China were included in the study. Anxiety scores were collected and analyzed using the IZOF model to describe and explain the MPA. Thirty students in total were enrolled and showed different anxiety scores of cognitive state anxiety (CA), somatic state anxiety (SA), and self-confidence (SC) in four performances. Performance scores of not less than 90 were predicted in 60% of participants by more than one of three subscales in IZOF. The CA and SA scores fell primarily above or within the IZOF, while the SC scores fell below the IZOF. In conclusion, the IZOF model provides information for both piano teachers and pianists to help review their anxiety intensity and predict to some extent their performances.